The Gale encyclopedia of native American tribes - Malinowski, Sharon; Sheets, Anna (Mich., 1998)
Contents: v.1. Northeast, Southeast, Caribbean. -v.2. Great Basin, Southwest, Middle America. -v.3. Arctic, Subarctic, Great Plains, Plateau. -v.4. California, Pacific Northwest, Pacific Islands Incl. bibl.